Memories of the Scientist, the Teacher, the Lecturer, the Pedagogue and the Educator Professor Kosta Dimitrov Pergelov - Hristina Oreshkova (International Business and Accounting Research Journal, 2022)
The article is dedicated to the 100th anniversary of the birth of the prominent Bulgarian scientist economist and accountant Kosta Dimitrov Pergelov. The primary purpose of the article is to reveal the author’s deep gratitude and appreciation for the Honourable Professor Kosta Dimitrov Pergelov – Doyen of contemporary Bulgarian accounting science and practice, Doyen of the accounting education and postgraduate studies and qualification in Bulgaria. The article is an expression of the author’s admiration and deep esteem for the highly humane and noble work and remarkable scientific creativity and long teaching activity of Professor Kosta Dimitrov Pergelov. Following the author’s aim and objectives, the article highlights essential features of the Professor’s intellectual and spiritual image, his vivid and fascinating personality, moral and ethical advancement, and erudition. The author reveals the favourable and fruitful influence of Professor Kosta Pergelov as a scientist, academic, pedagogue, and educator for generations of students, young scholars and researchers, and lecturers. The enormous contribution of Professor Kosta Pergelov to the development and rise of contemporary accounting as a science and practice, to the accounting education, and to the establishment and functioning of the postgraduate education and qualification system in Bulgaria is also highlighted and emphasized. The author recreates valuable memories of her long-term collaboration with Professor Kosta Pergelov and relies on the scientific works created by the Professor, which have turned into emblematic milestones of contemporary Bulgarian accounting science, and into a substantial part of its golden fund. The article reveals the author’s experience gained throughout the long period of educational and scientific collaboration with Professor Kosta Dimitrov Pergelov in the field of teaching fundamental academic disciplines like the theory of accounting, principles of accounting, fundamentals of accounting, accounting and balance sheet analysis and others. The article is based on personal impressions and thorough research of Professor Kosta Dimitrov Pergelov’s scientific works. The close working cooperation allows the author to present the charismatic and fascinating personality of Professor Kosta Dimitrov Pergelov. The article is intended to acquaint current generations of students of finance, accounting, control and analysis, and other present and future economists and accountants, theoreticians, and practitioners, with the enormous scientific contribution of Professor Kosta Pergelov to contemporary accounting science, the accounting practice and the system of accounting education and postgraduate studies and qualification in Bulgaria.